Composition of the Essential Oil of Endemic Salvia cryptantha Lamiaceae Montbret & Aucher Ex Bentham from Turkey - Dogan, Gülden; Hayta, Şükrü; Demirpolat, Azize; Bagcı, Eyüp (Hacettepe Üniversitesi, 2017)
In this study, the essential oil composition of Salvia cryptantha Montbret & Aucher ex Bentham from Turkey. The qualitative and quantitative essential oil contents of the this species was determined and compared with each other. The chemical composition of essential oils obtained by hydrodistillation of Salvia cryptantha was investigated by GC and GC-MS. The essential oils yield is 0.4 v/w . Sixty three constituents were comprised the 98.7% of the total essential oil extracted from the Salvia cryptantha. The predominant compounds of Salvia cryptantha were determined as 1.8-cineole 21% , camphor 19.1% , ?-pinene 12.5% , camphene 8.7% .

B u çalışmada, Türkiye için endemik Salvia cryptantha’nın Montbret & Aucher ex Bentham uçucu yağ kompozisyonu analiz edildi. Bu türün nicel ve nitel uçucu yağ içeriği belirlendi ve birbirleriyle karşılaştırıldı. Uçucu yağın kimyasal kompozisyonu su damıtımı yardımıyla belirlendi ve GC/GC-MS kullanılarak incelendi. Uçucu yağ verimi 0.4% v/w ’dir. Salvia cryptantha’tadan 63 bileşenin elde edilen toplam uçucu yağın %98.7’sini oluşturduğu görüldü. Salvia cryptantha’da temel bileşenler 1.8-sineol %21 , kafur %19.1 , ?-pinen %12.5 ve kamfen %8.7 olarak belirlendi
Türkiye’de Endemik Salvia cryptantha Lamiaceae ’nın Montbret & Aucher Ex Bentham Uçucu Yağ Kompozisyonu